2023
DOI: 10.1111/ele.14185
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for the match‐mismatch hypothesis across terrestrial trophic interactions

Abstract: Climate change has led to widespread shifts in the timing of key life history events between interacting species (phenological asynchrony) with hypothesized cascading negative fitness impacts on one or more of the interacting species—often termed ‘mismatch’. Yet, predicting the types of systems prone to mismatch remains a major hurdle. Recent reviews have argued that many studies do not provide strong evidence of the underlying match‐mismatch hypothesis, but none have quantitatively analysed support for it. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Shifts in plant phenology are a widespread fingerprint of global climate change, yet studies have shown the implications of this shift for a somewhat narrow set of species interactions, primarily pollination and herbivory (Kharouba et al 2018, Kharouba and Wolkovich 2023). However, flowers can host a much broader set of species interactions, and in this study, we demonstrate an important indirect effect of plant phenology on the mutualistic interactions between a rare lycaenid, Celastrina humulus , and its attendant ants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in plant phenology are a widespread fingerprint of global climate change, yet studies have shown the implications of this shift for a somewhat narrow set of species interactions, primarily pollination and herbivory (Kharouba et al 2018, Kharouba and Wolkovich 2023). However, flowers can host a much broader set of species interactions, and in this study, we demonstrate an important indirect effect of plant phenology on the mutualistic interactions between a rare lycaenid, Celastrina humulus , and its attendant ants.…”
Section: Discussionmentioning
confidence: 99%
“…Given that larval diet can have carry-over effects on adult fitness in lepidoptera (Niitepõld et al 2014, Niitepõld and Boggs 2022), mismatches with host plant phenology could scale up to impact lycaenid population dynamics. However, studies from flower-feeding herbivores are one of several gaps in the existing literature on phenological mismatches (Kharouba et al 2018, Kharouba and Wolkovich 2023). Understanding these interactions may be especially important in the context of global change, including declines in insect abundance (Soper Gorden and Adler 2018, Hamann et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such effects, however, can often be hard to prove empirically as they might be delayed and/or initially small (van Gils et al, 2016). These studies also call for a framework that includes better hypothesis testing and greater mechanistic understanding of the different factors that may contribute to consequences of phenological mismatch (Kharouba & Wolkovich, 2023;Samplonius et al, 2021;Visser & Gienapp, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they risk phenological mismatch (Cohen et al, 2018;Visser & Holleman, 2001) that can potentially lead to poorer individual reproductive success, population viability, and eventually decline (Both et al, 2006;Lane et al, 2012;Post & Forchhammer, 2008;Rosenberg et al, 2019;van Dis et al, 2023;Youngflesh et al, 2023). Some recent meta-analyses raised doubts on a causal relation due to the difficulty of finding empirical support for the negative effects of the match-mismatch hypothesis for population dynamics in many instances (Kharouba & Wolkovich, 2023;Samplonius et al, 2021;Visser & Gienapp, 2019). Such effects, however, can often be hard to prove empirically as they might be delayed and/or initially small (van Gils et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Especially if the temporal distribution of the resource is narrow [7], such mismatch can have severe fitness consequences for the individuals of the consumer species [8] and therefore leads to directional selection on its phenology [6,9]. Note however that this does not mean that there will also be effects on mismatches at the population level [10] and indeed such effects are not often demonstrated [11]. Increasingly strong directional selection on phenology has been shown for many wild populations [4], and since the rate of climate change is predicted to increase [12], it is crucial to understand drivers of temporal patterns in directional selection to forecast its future impact on evolutionary processes in wild populations.…”
Section: Introductionmentioning
confidence: 99%